2012
DOI: 10.1158/0008-5472.can-12-0639
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Modulates the Levels of Reactive Oxygen Species by Targeting SOD3 and TNFα

Abstract: MicroRNA-21 (miR-21) is an oncomir overexpressed in most human tumors in that it promotes malignant growth and progression by acting on multiple targets. Here, we broaden the impact of miR-21 in cancer by showing that it regulates the formation of reactive oxygen species (ROS) that promote tumorigenesis. Key targets of miR-21 in mediating this function were SOD3 and TNFa. We found that miR-21 inhibited the metabolism of superoxide to hydrogen peroxide, produced either by endogenous basal activities or exposure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 20 publications
(25 reference statements)
3
117
0
Order By: Relevance
“…miRNAs also influence the ROS defense system. miR-21 inhibits the metabolism of superoxide to H 2 O 2 by directing attenuating SOD3 or by indirectly reducing SOD2 levels (208). In an epithelial cell line, miR-30b regulates ROS levels by targeting CATs (58).…”
Section: Protecting Mitochondrial Functionmentioning
confidence: 99%
“…miRNAs also influence the ROS defense system. miR-21 inhibits the metabolism of superoxide to H 2 O 2 by directing attenuating SOD3 or by indirectly reducing SOD2 levels (208). In an epithelial cell line, miR-30b regulates ROS levels by targeting CATs (58).…”
Section: Protecting Mitochondrial Functionmentioning
confidence: 99%
“…The resulting inhibition of VDAC reduces ion flux between the mitochondria and the cytosol, resulting in mitochondrial hyperpolarization and an increased threshold for the opening of the MPTP. Intriguingly, Zhang et al have demonstrated that miR-21 also modulates cellular ROS levels by targeting SOD2 and SOD3, the proteins which are responsible for reduction of more reactive free radical anion superoxide to the less reactive hydrogen peroxide (101). By promoting the accumulation of ROS, miR-21 up-regulation induces a cytosolic environment that mimics that which would occur after a period of hypoxia, while the additional role of miR-21 in MPTP regulation ensures that the cell is prepared to withstand such cytotoxic effects without succumbing to apoptosis.…”
Section: Targeting Mitochondrial Apoptosis Via the Akt/hk-ii Signalinmentioning
confidence: 99%
“…Nonetheless, all of these are potential contributors to the hypoxic program, and several have been shown to participate in metabolic regulation (Table 1). Furthermore, miRNA activity has been uncovered at nearly every level of the mitochondrial response to hypoxia, from HIF stabilization (9,32,46,88), to the induction of anaerobic glycolysis (44,53,55,82,101), to the suppression of oxidative phosphorylation (13,28,56,71). Thus, hypoxamirs represent key intermediaries between hypoxia, HIF, and the mitochondrial phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative stress response is a pathway which provides and activates several antioxidant proteins and enzymes such as glutathione or superoxide dismutase [42], both of which are directly regulated by different miRNAs to detoxify oxidative stress metabolites [47], [48]. Both, the heat stress response and the UPR are pathways meant to cope with the accumulation of misfolded proteins, mostly in the endoplasmic reticulum [40].…”
Section: Resultsmentioning
confidence: 99%